IMPACT OF ROTATORY VESTIBULAR STIMULATION AND CURCUMA LONGA ON SPATIAL LEARNING AND MEMORY IN WISTAR ALBINO RATS - Np, Devi; Mukkadan, Joseph Kurian (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study was aimed at investigating the effect of rotatory vestibular stimulation and the capacity of the powerful antioxidant curry spice Curcuma longa (turmeric) on neuromorphological and brain cholinesterase activity in rats to analyze the behavioral changes and cognition in healthy Wistar albino rats. Methods: A total of 72 adult male Wistar albino rats were randomly assigned into four groups. For Group A (control group) neither vestibular stimulation nor the turmeric was administered, Group B (rotatory vestibular stimulated group), rotatory vestibular stimulation was given for 5 minutes in a rotatory vestibular apparatus at a rate of 50 revolutions per minute in clockwise direction for 30 days, Group C (turmeric alone) treated with 2 mg/kg of turmeric for 30 days, Group D (turmeric+vestibular), treated with 2 mg/kg of turmeric followed by 5 minutes of rotatory vestibular stimulation for 30 days. Results: Group B shows improvement in learning via a reduction in number of trails for acquisition and retention, and an increase in dendritic branching points and intersections and also a reduction in acetylcholinesterase level. Conclusion: Rotatory vestibular stimulation provides improvement in cognition via neuromorphological and biochemical changes than rotatory vestibular stimulation and turmeric in combination and turmeric alone, though there is no significant difference between the treated groups. Rotatory vestibular stimulation in combination with turmeric (Group D) shows a nonsignificant increase in dendritic arborization ensures a long lasting promising effect in cognition enhancement through a long period of treatment. Further detailed study on combination of rotatory vestibular stimulation and turmeric is required to explore the mechanism of therapeutic action of this intervention as a useful remedy for the management of cognitive disorders. Keywords: Rotatory vestibular stimulation, Turmeric, Learning and memory, Hippocampal neurons